Underestimated Value of Sarcopenia in Gastric Cancer Surgery - Lukšta, Martynas; Lukšaitė-Lukštė, Raminta; Baušys, Augustinas; Strupas, Kęstutis (Lietuvos chirurgija, 2020)
Surgery remains the only potentially curative option for gastric cancer, although it is related to high postoperative morbidity and mortality rate. Approximately every second gastric cancer patient is diagnosed with sarcopenia, which is a significant risk factor for postoperative complications and poor long-term outcomes. However, sarcopenia is underestimated in routine clinical practice, since it remains the interest of clinical trials. Sarcopenia diagnostic criteria are not fully standardized, but it consists of tests for muscle strength, quantity and quality. They include grip strength, chair stand test, computed tomography, magnetic resonance imaging, ultrasound, bioelectrical impedance analysis and densitometry tests. Regarding the growing evidence for sarcopenia impact on surgical gastric cancer treatment results, it is a high probability that sarcopenia assessment will come to routine clinical practice. Although, until then there is a need for further clinical trials to standardize the diagnostic and to find effective treatment strategies.